Discovery of the Major Mechanism of Global Warming and Climate Change - Rivera, Paul C.; Khan, Tariq Masood Ali (Journal of Basic & Applied Sciences, 2012)
Statistical analysis of the number of destructive earthquakes versus global temperature and greenhouse gases revealed very significant correlations. The motion of the North Pole, deduced from the geomagnetic polar shift data, is highly correlated with major earthquakes. This is an indication that the frequent occurrence of major earthquakes had increased earth’s obliquity and induced global warming and possibly emission of greenhouse gases. It was shown by a simple model developed here that seismic-induced oceanic force could enhance the obliquity leading to increased solar radiative flux on earth. The increase of the absorbed solar radiation due to polar tilt was also confirmed by SOLRAD model which computed a net gain of solar radiative forcing due to enhanced obliquity. SOLRAD also revealed a poleward gain of solar radiative flux which could have facilitated the observed polar amplification of global warming. Multiple regression analysis also showed that polar shift and solar irradiance played a major role in the temperature rise and CO2 increase in recent years. The analysis showed that obliquity change due to North Pole shift and total solar irradiance accounted for 63.5% and 36.4% respectively, while CO2 changes accounted for 0.1% of the observed global warming. Preliminary simulations conducted with EdGCM climate model also showed that enhanced obliquity increases the absorbed solar radiative flux, surface air and ocean temperatures, and decreases ocean ice cover. This study confirmed in several ways that earthquake-perturbed obliquity change, and not greenhouse effect, is the major mechanism governing the present global warming and climate change problem.